Effectiveness of Drip Irrigation Systems in Organic Chili Cultivation under Land Constraints - Ida Sugeng Suyani (Agriculture Journal, 2025)
Chili peppers (Capsicum spp.) play a key role in Indonesia’s horticultural economy, yet their cultivation—particularly under organic systems—faces persistent challenges related to land scarcity and efficient water management. This study aimed to evaluate the performance of drip irrigation compared with conventional watering methods for organic red chili grown under limited-land conditions. A controlled screen-house experiment was conducted using a 2×3 factorial RCBD with two irrigation methods (drip and conventional) and three water-dose levels (80%, 100%, and 120% ETc). Growth traits, water use efficiency (WUE), yield, and fruit quality parameters were measured. The results showed that drip irrigation combined with the optimal 100% ETc water dose significantly improved physiological stability, plant growth, total yield (12.35 t/ha), and WUE while minimizing water loss. Over-irrigation at 120% ETc reduced plant productivity, emphasizing the importance of precise water dosing. Incorporation of secondary climate and soil data from BMKG and ISRIC supported the broader applicability of the findings to West Java and similar peri-urban regions. Overall, the study demonstrates that precision drip irrigation provides a sustainable strategy to optimize resource efficiency and maintain high fruit quality in organic chili production on restricted land.